Professional Nursing Competence in Contemporary Healthcare: A Qualitative Study of Knowledge, Skills, and Attitudes Integration - Suprapto Suprapto; Yohan Trayanus Lasarus Djaha (Utan Kayu Publishing, 2026)
The increasing complexity of contemporary healthcare requires nurses to integrate knowledge, clinical skills, and professional attitudes to ensure high-quality and safe patient care. However, limited qualitative evidence exists on how this integration is experienced and enacted in real-world clinical settings. This study aims to explore nurses’ lived experiences in integrating knowledge, skills, and attitudes as core components of professional competence in contemporary healthcare practice. Methods: A qualitative study with a phenomenological approach was conducted among 18 registered nurses working in hospital and primary healthcare settings. Participants were purposively selected based on their clinical experience and direct involvement in patient care. Data were collected through in-depth semi-structured interviews and analyzed using thematic analysis following Braun and Clarke’s framework. Results: The findings revealed that professional nursing competence is a dynamic and integrative process shaped by individual and organizational factors. Seven main themes were identified: adaptive clinical reasoning, interprofessional collaboration, professional knowledge integration, clinical skills proficiency, ethical and professional attitudes, organizational support, and reflective practice. These themes demonstrate how competence is constructed through experiential learning, teamwork, and contextual influences within healthcare environments. Conclusion: Professional nursing competence is a multidimensional and context-dependent phenomenon that extends beyond individual capability. Strengthening the integration of knowledge, skills, and attitudes requires supportive organizational environments, collaborative practice, and continuous reflective learning. These findings provide important implications for nursing education, policy, and clinical practice in enhancing competency-based healthcare delivery.